Differential Transcriptional Alterations In Detoxification Genes In Parkinson’s Disease In Egypt - Shebl, Nourhan (AUC Knowledge Fountain, 2023)
PD is the most common motor neurodegenerative disease worldwide. The underlying cause of PD is still unknow, owingthis to the complexity of the disease. Often, genetics and environmental factors are collaborating in the initiation of the disease. Despite the diversity of its genetical and environmental profiles, the Egyptian population is one of the mostunderrepresented population in terms of PD research. In this study, we investigated PD through various perspectives tohighlight the complexity of the disease in Egypt, taking into consideration the diversity of the Egyptian population. We recruited PD patients and reference controls from 4 governorates: Cairo, Giza, Alexandria, and Mansoura to study their genetical and environmental profiles. We collected blood samples and complete clinical, medical, occupational, residential, and family history. Then, we performed several assays such as gene expression, Kompetitive allele specificPCR (KASP) for genotyping, heavy metals assay targeting Al, Cd, Cu, Cr, Mn, Pb, and Ni, and non-target metabolomics. Finally, we statistically correlated and categorized the results in alignment with the clinical data and the completecollected history. Our findings and observations are very promising. We observed that prevalence of the EOPD is higherthan that in other countries. We, also, observed that there is a possible correlation between each of LRRK2 and BCHEK-variant, and pesticides exposure in PD. In our study, we highlighted the complex genetic profile within the Egyptian population in respect to our targeted PD-related genes such as LRRK2, APOE4 and MAPT. Nevertheless, our heavy metals results showed diversity in the distribution among the governorates. On the other hand, and for the first time in PD, we studied the metabolism of phenylalanine via PAL enzyme. This metabolism showed to shift the reaction from producing L-dopa and DA to producing trans cinnamate and ammonia, depriving the neurons from DA and leading to apossible neurotoxicity and, thus, neurodegeneration. Another interesting finding is that we identified a metabolite, 5 Deoxy-5-Methylthioadenosine, that is significantly lower in the K- variant carrier PD patients compared to the non-carrier patients. The reduced levels of the latter metabolite indicate lower glutathione, detoxifying enzyme levels, leaving the K-variant carrier PD patient with higher risk. All these findings and observations showed how complex is the PD profile inthe Egyptian population.